61 Burnout in Core Surgical Trainees and Potential Use of Mindfulness. (12th October 2021) - Farrell, S; Khadum, M; Molodynski, A
Abstract: Aim: Surgical trainees deal with long hours and stressful work content. We aimed to assess the burnout levels in London trainees, and trial a mindfulness intervention. Method: London core surgical trainees (CST1) were asked to complete an online survey including validated burnout scoring system (Oldenburg Inventory). 54 of a possible 78 trainees responded (69%). We then asked them to take part in a 2-week mindfulness intervention (approximately 5 minutes a day using the app Headspace). We later resurveyed. Results: 60% of trainees who answered the survey feel 'somewhat' or 'completely' burnt out. Oldenburg burnout inventory calculates 85% of trainees to be 'disengaged' and 93% 'exhausted'. 13/54 trainees completed the mindfulness training. 10 out of 13 trainees found this to be 'somewhat' or 'massively' helpful for burnout. Conclusions: A high percentage of year one surgical trainees can be categorised as burnt out. The low uptake of mindfulness may speak to lack of capacity trainees have to invest in resources that will self-resolve this. We cannot say with significance whether mindfulness helped burnout (and length of trial could be too short) but the majority who did trial report positive experience with mindfulness.